Editor's Choice – Multicentre Outcomes of Redo Fenestrated/Branched Endovascular Aneurysm Repair to Rescue Failed Fenestrated Endografts. (November 2021) - Karelis, Angelos; Haulon, Stéphan; Sonesson, Björn; Adam, Donald; Kölbel, Tilo; Oderich, Gustavo; Cieri, Enrico; Mesnard, Thomas; Verhoeven, Eric; Dias, Nuno; ,; Marqués, Pablo; et al.
Abstract : Objective: To report the outcomes of redo fenestrated and/or branched endovascular aortic repair (F/BEVAR in FEVAR) to rescue previous failed FEVAR. Methods: Retrospective review of all consecutive patients undergoing F/BEVAR in FEVAR at eight aortic centres including pre-, intra-, and post-operative data according to a pre-established protocol. Follow up consisted of at least yearly computed tomography angiography. Values are presented as median and interquartile range, and survival as estimate ± standard error in percentage. Results: 18 male patients (76 years old; range 69 – 78 years) receiving FEVAR involving two (two or three) target vessels between 2006 and 2016 underwent F/BEVAR in FEVAR between 2012 and 2019 (aneurysm diameter of 63 mm; range 56 – 69 mm). Median interval between the procedures was 53 (29 – 103) months. The indication for F/BEVAR in FEVAR was type Ia endoleak in 16 cases (eight isolated and eight combined with graft migration), one graft migration without endoleak and one migration with significant proximal aortic expansion. F/BEVAR in FEVAR involved all patent renovisceral arteries and had an operating time of 260 (204 – 344) minutes. Technical success was achieved in 15 (83%) cases. There was a failure to bridge one renal artery, one renal capsular bleed with the subsequent need for renal artery embolisation within 24 hours and one persistent type Ib endoleak despite iliac extension. There was no peri- or in hospital death. Two patients developed spinal cord ischaemia, one transient paraparesis and one permanent paraplegia. The latter occurred in a non-staged procedure where spinal drainage was used. During a follow up of 27 (7 – 39) months, three (17%) patients underwent late re-interventions. Overall survival at 24 months was 70 ± 11% with no aneurysm related death and a secondary clinical success at 24 months of 84 ± 11%. Conclusion: F/BEVAR in FEVAR is a technically challenging but feasible solution to rescue failed FEVAR. The outcomes are promising in many aortic centres but need to be confirmed by further studies with longer follow up.